Solvothermal Syntheses, Crystal Structures, and Luminescent Properties of Two New Cadmium(II) Coordination Polymers Based on Rigid / Flexible Dicarboxylate and N, N′‐Bis(4‐pyridyl)‐1, 4, 5, 8‐naphthalenetetracarboxydiimide1. Issue 5 (25th February 2015) - Feng, Xiuling; Chen, Wanping; Xiang, Bolin
Abstract In order to investigate the effect of the organic ligands on the structures of coordination polymers, two new cadmium(II) coordination polymers based on the different dicarboxylate ligands, namely [Cd2(bpdc)2(DPNDI)2]·3H2O·NMF (1) and [Cd(obb)(DPNDI)] (2) [H2bpdc = biphenyl‐4, 4′‐dicarboxylate, H2obb = 4, 4′‐oxybis(benzoic acid), DPNDI = N, N′‐bis(4‐pyridyl)‐1, 4, 5, 8‐naphthalene tetracarboxydiimide, and NMF = N‐methylformamide), were synthesized under solvothermal condition and further characterized. Complex 1 shows a twofold interpenetrated pcu topology. Complex 2 possesses a two‐dimensional (2D) layer structure with –ABCD– stacking sequence. Furthermore, the luminescent properties of complexes 1 and 2 are investigated.